2019
DOI: 10.1002/ceas.12133
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors to Earning Tenure Among Black Male Counselor Educators

Abstract: The authors used a phenomenological research design and a critical race theory lens to examine interviews with 8 Black male counselor educators and learn what contributed to their earning tenure. Participants described requisite personal dispositions and institutional support as contributing factors. Recommendations include facilitating programmatic sociocultural awareness, assessing faculty experiences, and coordinating mentoring opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…For example, the idea of a space for growth, development, rest, and recovery is like what Vereen et al (2017) described in their investigation of Black existentialism and its connection to a homeplace for people of color. Additionally, the results of this heuristic inquiry connect to what Hannon et al (2019) found when they shared that in order to be supportive of the development of Black male counselor educators, attention needed to be directed toward nontraditional ways of support and intervention on their behalf, given that they are less represented in counselor education programs and in academia. Our results indicate that the overall experience evolved into something altogether different that transformed over time to not only include the enhancement of but also further advance a unique set of connections for a diverse group of Black men.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…For example, the idea of a space for growth, development, rest, and recovery is like what Vereen et al (2017) described in their investigation of Black existentialism and its connection to a homeplace for people of color. Additionally, the results of this heuristic inquiry connect to what Hannon et al (2019) found when they shared that in order to be supportive of the development of Black male counselor educators, attention needed to be directed toward nontraditional ways of support and intervention on their behalf, given that they are less represented in counselor education programs and in academia. Our results indicate that the overall experience evolved into something altogether different that transformed over time to not only include the enhancement of but also further advance a unique set of connections for a diverse group of Black men.…”
Section: Discussionsupporting
confidence: 52%
“…Participants in the study indicated that their social justice orientation directly influenced their persistence and resilience as minoritized people overall and in counselor education programs. Likewise, Hannon et al (2019) found that tenured Black male counselor educators reported specific personal dispositions (e.g., openness to mentorship, in-depth personal and environmental awareness, clarity of purpose) and institutional support (e.g., clear expectations, active mentorship) were key to earning tenure. To support Black male counselor educators' success as faculty, the authors encouraged counseling program administrators to be transparent about program, department, and institutional culture (i.e., sociopolitical awareness); to systematically and frequently assess faculty experiences; and to coordinate mentoring programs for Black male and other minoritized counselor educators.…”
Section: Pathways To and Fulfillment In The Professionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rather than presenting one study after another in a linear fashion, the description of existing literature should be integrated to support the important points of the authors' case for the study (Balkin & Kleist, 2017). In an integrated literature review, authors will not describe each cited study but instead will use particular sources to support important claims (e.g., an author could write, "Both personal dispositions and institutional support contribute to tenure acquisition among Black male counselor educators"; Hannon et al, 2019). Authors are encouraged to create an outline prior to writing the literature review section in which they clearly articulate the main points of their case for the importance of the study and identify existing literature supporting each point.…”
Section: Features Of a Strong Literature Reviewmentioning
confidence: 99%
“…Alvarado et al (2019) sought to better understand the experiences of students providing counseling services in Spanish as they completed an English‐language counselor education programs. Other research focused on Black male counselor educators who had received tenure, to learn more about how personal dispositions and institutional supports contributed to promotion (Hannon et al, 2019), whereas Shavers and Moore (2019) addressed Black female doctoral student experience at predominantly White institutions and their perceptions related to being a “perpetual outsider” in unwelcoming spaces, experiences of tokenism, and other issues influencing their education and identity. Finally, two qualitative studies focused on spiritual dimensions of quality of life attended to by rehabilitation and other counselor educators to raise awareness and understanding of the importance of addressing spiritual well‐being in training (Lu et al, 2019) and wellness‐focused supervision inclusion of wellness principles to assist supervisees in understanding experiences of military service members whom trainees may work with, so as to create responsive supervision environments that foster growth and development (Briggs & Hayden, 2019).…”
Section: Stakeholder Experiencesmentioning
confidence: 99%